Systemic IL-1β and TNF-α Productions of E. coli Lipopolysaccharide-Induced Periodontitis Model on Rats - Alma Linggar Jonarta; Widya Asmara; Indwiani Astuti; Regina TC Tandelilin (The Indonesian Journal of Dental Research, 2010)
Periodontal disease, a common inflammatory oral disease involved periodontal tissues, has been linked with the evidence of some systemic disorders. Recently, periodontal disease has been suspected as a trigger of systemic disorders. Penetration of bacterial products, such as lipopolysaccharide (LPS) may reach into deeper periodontal tissues. Therefore there may affect systemic blood and cytokines production. Interleukin-1β (IL-1β) and Tumour Nuclear Factor-α (TNF-α) are known as pro-inflammatory cytokines. The production of systemic IL-1β and TNF-α of E. coli lipopolysaccharide-induced periodontitis model on rats was investigated in this research. Fifteen male Wistar rats, aged 6-8 weeks used for this study were divided into 3 groups. For group 1 and 2, silk ligature 3/0 were inserted in interdental area between upper right molar 1 and 2. First and second group received solution containing 10μg/ml and 1mg/ml E. coli lipopolysaccharide, respectively, mixedwith 2% carboxymethylcellulose (CMC) diluted in 100μl of phosphate buffer saline (PBS). The solution was topically applied on gingival tissues around the gingival sulcus, a single topical application of solution onceper 2 days for 14 days. Untreated subjects were used as negative control. On day 15, the blood was collected from vena orbitalis, and rats were sacrificed. The blood serum of each group was divided into 2 groups andcultured for 4 hours with or without 20μl of 100ng/ml of E. coli LPS. ELISA techniques were used to measure the cytokine productions of the supernatant. The data was analysed using Repeated Measure ANOVA. This study showed that there was a significant increase of IL-1β production on low dose of LPS compared to control and high dose of LPS groups (p<0.05). Whereas TNF-α not significantly showed increasing trend. The increasing trend of pro-inflammatory cytokine productions, such as IL-1β and TNF-α, on LPS-induced periodontitis model in this experiment supports the previous studies about the contribution of periodontal disease in the pathogenesis of systemic diseases.